KAJIAN POLA WACANA KEKERASAN DAN USAHA PREVENTIF SERTA ANTISIPATIF MENGATASI PERKELAHIAN PELAJAR - SRI SUKARDI, JOKO (FOUNDASIA, 2015)
A competetion an cooperation are two different things hut they should be able to be combined in developing the social life of school, for the competetion tends to bring about the potential growth of conflict sources. The Conflict on a result of the school informal symbols is in the contrary to the school forrnul symbols. The preventive and anticipulive effort if it has been implemented by the school, is necessary to he continued for socialization. The cumpetefion among the schools can be modified to be a cooperation, in which each school with patenfial students is joined with other school Potential student to have a training together, so that it seems there is no competition, but show more in cooperation.